Idiosyncratic contagion between ETFs and stocks: A high dimensional network perspective - Wang, Yu; Sun, Yiguo (Journal of Financial Stability, 2025)
This paper examines the return spillovers between Exchange-Traded Funds (ETFs) and stocks. While traditional approaches focus on proportional relationships between ETFs and their underlying assets, we develop a high-dimensional network framework that captures spillover effects between any ETF-stock pair, regardless of their compositional relationship. By separating idiosyncratic and systematic risks, we investigate potential drivers of contagion. We document substantial heterogeneity in spillover patterns across sectors, which is previously unaddressed in the literature. Sectors such as Utilities and Real Estate exhibit robust spillovers to both their component stocks and assets in other sectors. Conversely, in sectors such as Consumer Discretionary and Finance , cross-sector influences dominate intra-sector ETF-constituent linkages. Our results also highlight that during periods of high market volatility, sources of idiosyncratic contagion become more diverse, suggesting the need for broader market surveillance beyond the few most influential ETFs.